Perspectives on Additive Manufacturing - Bourell, David L. (Annual Review of Materials Research, 2016)
Additive manufacturing (AM) has skyrocketed in visibility commercially and in the public sector. This article describes the development of this field from early layered manufacturing approaches of photosculpture, topography, and material deposition. Certain precursors to modern AM processes are also briefly described. The growth of the field over the last 30 years is presented. Included is the standard delineation of AM technologies into seven broad categories. The economics of AM part generation is considered, and the impacts of the economics on application sectors are described. On the basis of current trends, the future outlook will include a convergence of AM fabricators, mass-produced AM fabricators, enabling of topology optimization designs, and specialization in the AM legal arena. Long-term developments with huge impact are organ printing and volume-based printing.
Keywords: current applications